Quantitative techniques for business : (operations research/management science quantitative/ decision science) - Sirug, Winston S. (Makati City, Philippines : Mindshapers Co. Inc., 2006)
This is an introduction to quantitative techniques for business/operations research/ management sciece. It is anticipated that the students have studied college algebra and probability and statistics.
Chapter 1 : System of linear equations and inequalities -- Chapter 2 : Linear programming : graphical method -- Chapter 3 : Linear programming : simplex method -- Chapter 4 : Linear programming : sensitivity analysis -- Chapter 5 : Transportation model -- Chapter 6 : Assignment model -- Chapter 7 : Network analysis -- Chapter 8 : Break-even analysis -- Chapter 9 : Forecasting -- Chapter 10 : Decision theory -- Chapter 11 : Inventory model.
Includes bibliographical references.
Keywords: MANAGEMENT -- MATHEMATICAL MODELS